Complex Movement Disorders in Ataxia with Oculomotor Apraxia Type 1: Beyond the Cerebellar Syndrome. (7th October 2020) - Pedroso, José Luiz; Vale, Thiago Cardoso; da Costa, Sophia Caldas Gonzaga; Santos, Mariana; Alonso, Isabel; Barsottini, Orlando Graziani Povoas
Background: Ataxia with oculomotor apraxia (AOA1) is characterized by early-onset progressive cerebellar ataxia with peripheral neuropathy, oculomotor apraxia and hypoalbuminemia and hypercholesterolemia. Case Report: A 23-year-old previously healthy woman presented with slowly-progressive gait impairment since the age of six years. Neurological examination revealed profound areflexia, chorea, generalized dystonia and oculomotor apraxia. Brain MRI revealed mild cerebellar atrophy and needle EMG showed axonal sensorimotor neuropathy. Whole exome sequencing revealed a mutation in the aprataxin gene. Discussion: AOA1 can present with choreoathetosis mixed with dystonic features, resembling ataxia-telangiectasia. This case is instructive since mixed and complex movement disorders is not very common in AOA1. Highlights: Ataxia with oculomotor apraxia type 1 (AOA1) is characterized by early-onset ataxia and oculomotor apraxia caused by variants in the APTX gene. Ataxia is usually not the sole movement abnormality in AOA1. Hyperkinetic movement disorders, especially chorea and dystonia, may occur. Mixed and complex movement disorders is not very common in AOA1. Patients with early-onset ataxia associated with mixed movement disorders should also be investigated for AOA1.